EFEKTIVITAS PENERAPAN MBS DITINJAU DARI ANALISIS SWOT DI SD NEGERI 6 PANJER - Chindytia; Ida Bagus Gede Surya Abadi; Gita Magnivicharia Lembut; Ni Kadek Della Aryastuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of Manajemen Berbasis Sekolah (MBS) is a strategic effort to improve the quality of education through independent, participatory, and transparent school management. However, its implementation has not been fully optimized due to the influence of various internal and external factors. This study aims to analyze the effectiveness of MBS implementation at SD Negeri 6 Panjer using a SWOT analysis approach. This study used a qualitative descriptive method with data collection techniques in the form of case study. The results showed that the school's strengths lie in participatory leadership, directed program management, and good cooperation with various parties. Weaknesses found include suboptimal program implementation and dependence on stakeholder participation. Opportunities come from support from agencies and the community, while threats include negative public perception and competition between schools. Overall, the implementation of SBM at SD Negeri 6 Panjer is quite effective, but still requires improvement in the consistency of program implementation and strengthening the evaluation system.